A Comprehensive Analysis of KIP Kuliah Scholarship Recipients Conditions in Central Java Private Universities - Arifin, Zaenal (Universitas Negeri Semarang, 2024)
This study aims to provide a description and analysis of data concerning KIP Kuliah scholarship recipients in private universities located in Central Java. The data for this research was obtained from KIP Kuliah managers at LLDIKTI Region VI Central Java. The research method employed in this study is quantitative research, involving a descriptive statistical analysis of the previously processed data. The analysis findings showed that the data on KIP Kuliah recipients at private universities in Central Java aligned with the recipient criteria outlined in the 2022 KIP Kuliah guidelines. The data analysis unveiled various effects and challenges faced by recipient students. To promote positive effects and tackle these challenges, it is recommended to provide appropriate support and recommendations.